First report of cyanobacterial bloom of Microcystis viridis (A. Braun) Lemmermann in Slovenia - Tina Eleršek (Acta Biologica Slovenica, 2009)
The presence of the cyanobacterial bloom of Microcystis viridis (A. Braun) Lemmermann is reported for the first time in Slovenia. After field sampling, and detailed microscopic observations, species analysis, chlorophyll content analysis, and cyanobacterial cyclic peptides were determined, the latter by high performance liquid chromatography (HPLC). Cells were found in colonies with limited amounts of more or less refractive mucilage. The average diameter of a cell was 4–7 µm. Three microcystins, two anabaenopeptins and planktopeptin BL 1125, were identified. The content of cyclic peptides in the bloom was in the range of 2.3–6.6 mg g–1 of cellular dry weight. M. viridis was dominant in the cyanobacterial bloom, other species being Micorcystis wesenbergii, Microcystis aeruginosa, Anabaena flos-aque, Anabaena spiralis, Aulacoseira granulata, Closterium sp., Euglena sp., Pediastrum duplex, Scenedesmus quadricauda, Staurastrum gracile, Trachelomonas volvocina, Trachelomonas hispida and Tetraedron limneticum. In keeping with previous studies the content of cyclic peptides in the cyanobacterial bloom was high enough to cause bloom lysis. This fact was also confirmed by field observation; not only bloom composition change, but after 8 days there was no visible cyanobacterial bloom on the Boreci reservoir surface, although no heavy rain or wind was observed during this period. The discovery of M. viridis bloom in Slovenia is very important, since toxic bloom constitutes a threat all over the World.